Case series of drug-induced open bite: Extrapyramidal symptoms related to psychotropic medications - Watanabe, Motoko; Tu, Trang Thi Huyen; Takao, Chihiro; Maeda, Chizuko; Nayanar, Gayatri Krishnakumar; Tominaga, Risa; Kimura, Yasuyuki; Takenoshita, Miho; Yoshikawa, Tatsuya; Sumi, Koji; Sumi, Satoko; Motomura, Haruhiko; et al. (Frontiers in Psychiatry, 2023)
Drug-induced open bite is found as one of the extrapyramidal symptoms with abnormal tonus of muscles, and rarely recognized in dentistry. This is a retrospective case study with the aim of investigating clinical characteristics including detailed complaints in the patients with drug-induced open bite. Of the outpatients who first visited psychosomatic dental clinic in Tokyo medical and dental university hospital between September 2013 and September 2022, the patients diagnosed as drug-induced open bite were involved in this study. The clinical characteristics including sex, age, detailed complaints, duration of illness, abnormal findings, psychotropic medications and other medications that were taken at the first examination, psychiatric comorbidities, the duration of psychiatric diseases and other medical histories were collected retrospectively by medical chart reviewing. Drug-induced open bite was found in 11 patients [female: 7, male: 4, median of age: 49 (36.5, 53) years old]. Difficulty in eating especially chewing was the major complaint (9/11, 81.6%) with the duration of illness as 48.0 (16.5, 66) months. Various degrees of open bite were observed. While some showed no occlusal contact on frontal teeth, some showed occlusal contact only on the second molars; moreover, jaw showed horizontal slide in a few patients. Three cases could be followed up for prognosis; while one case improved drug-induced open bite for 6 months follow-up, two cases did not improve and one showed extrusion of molars. All of them had psychiatric comorbidities with the most common diagnosis being schizophrenia (n = 5) and depression (n = 5) followed by insomnia (n = 1) and autism spectrum disorder (n = 1) including duplicated diagnosis. Nine patients (81.6%) had been undergoing the treatment with antipsychotics of which 3 patients were also taking antidepressants. Although drug-induced open bite is rare symptom, prudent medical interviews about symptoms, psychiatric comorbidities and psychotropic medication history besides oral assessment are necessary to provide precise diagnosis and appropriate managements over the collaboration between dentists and psychiatrists.